Racial and Ethnic Disparities in Breast Cancer Survival: Emergence of a Clinically Distinct Hispanic Black Population. Issue 3 (September 2021) - Goel, Neha; Yadegarynia, Sina; Lubarsky, Maya; Choi, Seraphina; Kelly, Kristin; Balise, Raymond; Kesmodel, Susan B.; Kobetz, Erin
Abstract : Objective: To understand the impact of Black race on breast cancer (BC) presentation, treatment, and survival among Hispanics. Summary of Background Data: It is well-documented that non-Hispanic Blacks (NHB) present with late-stage disease, are less likely to complete treatment, and have worse survival compared to their non-Hispanic White (NHW) counterparts. However, no data evaluates whether this disparity extends to Hispanic Blacks (HB) and Hispanic Whites (HW). Given our location in Miami, gateway to Latin America and the Caribbean, we have the diversity to evaluate BC outcomes in HB and HW. Methods: Retrospective cohort study of stage I-IV BC patients treated at our institution from 2005–2017. Kaplan-Meier survival curves were generated and compared using the log-rank test. Multivariable survival models were computed using Cox proportional hazards regression. Results: Race/ethnicity distribution of 5951 patients: 28% NHW, 51% HW, 3% HB, and 18% NHB. HB were more economically disadvantaged, had more aggressive disease, and less treatment compliant compared to HW. 5-year OS by race/ethnicity was: 85% NHW, 84.8% HW, 79.4% HB, and 72.7% NHB ( P < 0.001). After adjusting for covariates, NHB was an independent predictor of worse OS [hazard ratio:1.25 (95% confidence interval: 1.01–1.52), P < 0.041)]. Conclusions: In this first comprehensive analysis of HB and HW, HB have worse OS compared to HW, suggesting that race/ethnicity is a complex variable acting as a proxy for tumor and host biology, as well as individual and neighborhood-level factors impacted by structural racism. This study identifies markers of vulnerability associated with Black race and markers of resiliency associated with Hispanic ethnicity to narrow a persistent BC survival gap.